Valuing natural capital and ecosystem services toward the goals of efficiency, fairness, and sustainability - Costanza, Robert (Ecosystem services, 2020)
•Valuation is about assessing trade-offs toward a goal.•There are 3 goals for ES valuation: efficiency (E-value), fairness (F-value) and sustainability (S-value).•An integrated approach to valuation is needed toward these 3 goals.•A whole systems view of humans and the rest of nature is needed. Ecosystem services (ES) are the ecological characteristics, functions, or processes that directly or indirectly contribute to sustainable human wellbeing. The ecosystems that provide the services are ‘natural capital’ (NC) using the general definition of capital as a stock that yields a flow of services over time. But these concepts must be embedded in a whole systems view of the interdependencies between humans and the rest of nature, as espoused by ecological economics from its inception. Valuing NC and ES is therefore about assessing their contributions (in complex interaction with built, human, and social capital) toward the goal of sustainable wellbeing of the whole system of humans and the rest of nature. This recognizes that sustainable human wellbeing cannot be achieved without the wellbeing of the rest of nature. To achieve this, an integrated approach to valuation toward the three sub-goals of efficient allocation (E-value), fair distribution (F-value) and sustainable scale (S-value) is necessary. This article reviews these ideas, and discusses an agenda to improve understanding and valuation of NC and ES toward the goals of efficiency, fairness, and sustainability in a dynamic, whole systems context.